Paeoniflorin ameliorates ischemic injury in rat brain via inhibiting cytochrome c/caspase3/HDAC4 pathway - Liu Yi-fei; Zhang Lei; Wu Qi; Feng Lin-yin (Acta Pharmacologica Sinica, 2022)
Paeoniflorin (PF), a bioactive monoterpene glucoside, has shown a variety of pharmacological effects such as anti-inflammation and autophagy modulation etc. In this study, we investigated whether and how PF exerted a protective effect against ischemic brain injury in vivo and in vitro. Primary rat cortical neurons underwent oxygen/glucose deprivation/reperfusion (OGD/R) for 90 min. We showed that after OGD/R, a short fragment of histone deacetylase 4 (HDAC4) produced by caspase3-mediated degradation was markedly accumulated in the nucleus and the activity of caspase3 was increased. Treatment with PF (100 nM, 1 μM) significantly improved the viability of cortical neurons after OGD/R. Furthermore, PF treatment could maintain HDAC4 intrinsic subcellular localization and reduce the caspase3 activity without changing the HDAC4 at the transcriptional level. PF treatment significantly reduced OGD/R-caused inhibition of transcriptional factor MEF2 expression and increased the expression of downstream proteins such as GDNF, BDNF, and Bcl-xl, thus exerting a great anti-apoptosis effect as revealed by TUNEL staining. The beneficial effects of PF were almost canceled in HDAC4 (D289E)-transfected PC12 cells after OGD/R. In addition, PF treatment reduced the caspase9 activity, rescued the release of cytochrome c from mitochondria, and maintained the integrity of mitochondria membrane. We conducted in vivo experiments in 90-min-middle cerebral artery occlusion (MCAO) rat model. The rats were administered PF (20, 40 mg/kg, ip, 3 times at the reperfusion, 24 h and 48 h after the surgery). We showed that PF administration dose-dependently reduced infarction area, improved neurological symptoms, and maintained HDAC4 localization in rats after MCAO. These results demonstrate that PF is effective in protecting against ischemic brain injury and inhibit apoptosis through inhibiting the cytochrome c/caspase3/HDAC4 pathway.